Atividade Física Adaptada no contexto das matrizes curriculares dos cursos de Educação Física - Borella, Douglas Roberto (Universidade Federal de São Carlos, 2010)
Whereas deepen the discussion about teacher training in the field of physical culture and how this training also includes people with disabilities, this study sought to identify and analyze the characteristics of the disciplines that comprise the field of Adapted Physical Activity, contained on curricular of Physical Education courses in Brazil. For this purpose, we sought information and reflections on the discipline that involves people with disabilities in Higher Education Institutions (IES). Thus it was taken as an object of study, data derived from a questionnaire answered by the course coordinators of Physical Education. The study included 114 IES, 101 undergraduate courses in physical education courses and 59 Bachelor of Physical Education. The collected material was analyzed by using as a guiding principle the contribution of the discipline devoted to people with disabilities to the professional training in physical education. The first stage of the study consisted of mapping the IES that offer the course in Physical Education (BA and BS) through the identification and location. The initial search of the IES was given by the electronic addresses of official bodies regulating the education and the statistical and evaluative at all levels and types of education and, through electronic lists that include data on the relationship of all education courses Physics of Brazil. In possession of electronic addresses of the IES, sailed on the pages of each IES to locate the e-mail the coordinators of Physical Education courses address or legal guardians of the IES. The procedure of sending the questionnaire, the second stage took place during the months of April and May 2009. The analysis was done by breaking the following variables: name given to the discipline, working hours, menu, title of professor, supervised training in the discipline, practice as a curriculum component in the training and extension projects aimed at people with disabilities. Research results indicated expertise in Adapted Physical Activity required for teacher performance / physical education professional, which were discussed drawing on the researcher's gaze and theoretical framework that supports the study, seeking to establish relations with the initial and emerging needs in society. Considering the presented problem and considering the knowledge that a physical educator must submit to engender a coherent teaching practice, it is recommended a restructuring of the curriculum in the discipline that involves people with disabilities in physical education courses. From this perspective, it must be emphasized in the speech that the task of this discipline is not only to train professionals in the inclusive perspective, but also exposed that there is still the exception, and seek solutions for teaching and pedagogical education with people with disabilities. It's up to these professionals to develop skills to enable the acceptance of diversity in their sphere of action.
Keywords: Educação especial; Atividade física; Matriz curricular; Educação física; Atividade física adaptada; Adapted physical activity; Die curriculum; Physical education; Special education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL